An introduction to sociolinguistics - Wardhaugh, Ronald; Fuller, Janet M. 1962- (Blackwell textbooks in linguistics, 2021)
"Thoroughly updated and revised, An Introduction to Sociolinguistics, 8th Edition builds on this comprehensive introduction to the study of the relationship between language and society by refining the connections across underlying topics throughout the text. Expanding Ronald Wardhaugh's classic text, Janet Fuller has updated this eighth edition throughout and reorganized existing chapters whilst retaining its successful four section structure. Much needed expansion of the section on multilingualism has occurred to include a new chapter on issues of language and nation, colonialism, transnationalism, 'superdiversity', immigration, and globalization, in order to better focus on communication in the digital world and how this plays a role in the language use and identity-making in the age of globalization. An Introduction to Sociolinguistics, 8th EditioncircA continues to be the most indispensable and accessible introduction to the field of sociolinguistics for students in applied and theoretical linguistics, education, and anthropology."